Examining the impact of safeguard measures on local firms' performance - RACHMAN, Ayu Amalia (KDI School, 2022)
The textile sector is one of the important labor-intensive industries in Indonesia with an integrated supply chain, a high level of employment, and a significant share in manufacturing growth. In 2019, Indonesian government imposed safeguards on fabrics and yarn to protect domestic firms from an excessive number of imported products. This paper examines the impact of the safeguard measures on exports of Indonesian producers. I collected exports and imports data from Statistics Indonesia (BPS) from 2011 to 2021 and employ the Differences in Differences method (DID). The results provide evidence that the imposition of safeguards contributes to decreasing exports value by 31.8 percent and reduces imports value significantly by 26.5 percent. In this study, the safeguards policy is quite effective in slowing down the value of imports but it also has a drawback in decreasing exports. This finding may be used as a reference for the Indonesian government to formulate more effective policies in improving the performance of the local textile industries and decide on the extension of the safeguards for the next three years.
Thesis(Master) -- KDI School: Master of Public Policy, 2022
Keywords: Export and import controls--Indonesia; Textile fabrics--Indonesia